Killing Democracy Softly: Executive Privilege and the Defense of Democracy in the Americas. (25th November 2018) - Smith, Betsy L.
Abstract : Is the Organization of American States a "club of presidents?" A review of democratic crises from 1990 to 2016 lends support to the argument that the organization can be considered as such. This article adds to the literature by noting that the severity of democratic crises in Latin America is a key factor in the response. When there is a severe threat to democracy, there is likely to be a response, regardless of the origin of the crisis. The origin matters more during low‐level threats; the organization is more likely to respond to low‐level threats to presidents. Meanwhile, when the threat is from the president, it is less likely there will be a response. The findings from this article provide support for continued evaluations of the defense‐of‐democracy regimes in the Americas and show the potential for executives to erode democracy slowly and over time without significant responses from the Organization of American States, leading to low‐quality democracies in the region.